Professional ethics and its teaching in undergraduate courses in the health area (Research, Society and Development, 2019)
Care has been present since the beginning of human relations, being a social construction permeated by evolution and represented by the primordial ethical principles. The objective was to carry out a reflection through a bibliographical survey on the teaching of professional ethics in undergraduate courses in the health area, using bibliographies that approach this theme. It is a study of a reflexive nature, using as basis the authors of the area and bibliographic survey using the Portal of CAPES. It was observed that there are some difficulties regarding the teaching of health ethics, especially in relation to the direct link with the transmission of norms based on codes of ethics. Therefore, it is necessary to qualify the teaching of health ethics in order to train professionals who are capable and capable of making decision-making.